Early and Late Outcomes of Surgical Revascularization Procedures in Ischemic Cardiomyopathy - KETENCİ, Bülend and ÖZAY, Batuhan and GÜNEY, Mehmet and ÇİMEN, Serdar and GÜNAY, Rafet and GÖRÜR, Alper and ORHAN, Gökçen and DEMİRTAŞ, M. Murat and ÖZKUL, Vedat (Cerrahpaşa Medical Journal, 2014)
Management of patients with ischemic cardiomyopathy is rather complicated and also has a poor prognosis. Recently, substantial success rates have also been reported with off-pump technique in these high risk patients. Nevertheless, owing to the great advances that were achieved in traditional myocardial preservation and cardiopulmonary bypass techniques in the most recent years; a dilemma still remains regarding superiority of these techniques to each other in patients with ischemic cardiomyopathy. Thus, we have compared early and late results of these two techniques in this study. Study group included 25 operated patients who have an left ventricle ejection fraction of less than 30 % and left ventricular dilatation between 2001 and 2005. Groups 1 and 2 included patients that were operated with "off pump" and "cardiopulmonary bypass" techniques, respectively. Hospital mortality was 4% with 1 patient dying in Group 2. Durations of intensive care unit and hospital stays were shorter in Group 1. Two patients (1 from each group) died in the late postoperative period. Although midterm comparisons of both functional and angina classifications revealed better results in Group 2 patients, statistical significance wasn't present. Early and late outcomes of surgical revascularization procedures were satisfactory with both techniques in patients with ischemic cardiomyopathy. In this study, short term results seemed better in "off pump" patients, while late morbidity rate was lower for "cardiopulmonary bypass" group.